Improving adherence physical activity, quality of life and social support for activities in people with intellectual disabilities, through multimodal intervention (education + activity) - Pérez-Cruzado, David Francisco; Cuesta-Vargas, Antonio; Merchan Baeza, Jose Antonio; Roldán-Jiménez, Cristina (My University, 2014)
Background People with intellectual disabilities (ID) have a poor level of physical activity as they experience many barriers towards doing it (Bodde & Seo, 2009). Physical activity provides many benefits so there are studies to improve adherence to physical activity (Stanish & Frey, 2008). In our study we carried out a multimodal intervention (educational advice + physical activity) to improve adherence to physical activity in people with ID. Method. The sample consisted of 40 people with ID. They all received a multimodal intervention in ASPROMANIS INDUSTRIAL (Malaga, Spain), 2 hours per week for 8 weeks. The outcome measures were: IPAQ (International Physical Activity Questionnaire, WhoQoL Scale to find out about quality of life and SE/SS-AID to know self-efficacy and social support for activity. We measured fitness condition (strength, flexibility, balance and aerobic condition) through a physical fitness test (Functional reach test, single-leg stance with eyes open, single-leg stance with eyes closed, passive knee extension, calf muscle flexibility, anterior hip flexibility, functional shoulder rotation, time-stands test, partial sit-up test, handgrip test, two-minute step test). Results and discussion The results show that with the multimodal intervention, we did not find significant changes in physical activity by measuring with IPAQ (Mets/total) in people with ID. However, we detected an increasing trend [F=0.04(0,84). On the other hand we found significant changes in quality of life [F=4.18(0,04)], professional support[F=40,31(0)] and support for friends [10,09(0)]. Finally, in those with the fitness condition, we found an increasing trend towards flexibility, strength, balance and aerobic condition, and a significant increase in abdominal muscle strength [4.22(0,04)]. Conclussion The conclusion of our study is that a multimodal intervention over 8 weeks in people with ID can improve their quality of life and provide social support for activity, but without significant improvement in physical condition and physical activity. Randomized clinical trials and a higher sample will be needed to confirm this tendency towards improvement.
Keywords: Disminuidos mentales - Ejercicio físico; Intellectual; Disability; Intervention; Multimodal; Physical activity; Quality of life